2015
DOI: 10.1088/0953-4075/48/16/165003
|View full text |Cite
|
Sign up to set email alerts
|

Parity nonconservation effect in the resonance elastic electron scattering on heavy He-like ions

Abstract: We investigate the parity nonconservation effect in the elastic scattering of polarized electrons on heavy He-like ions, being initially in the ground state. The enhancement of the parity violation is achieved by tuning the energy of the incident electron in resonance with quasidegenerate doubly-excited states of the corresponding Li-like ion.We consider two possible scenarios. In the first one we assume that the polarization of the scattered electron is measured, while in the second one it is not detected.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…Moreover, these measurements demonstrated that utilizing theoretical estimates of the polarization transfer characteristics enables an accurate reconstruction of the incident beam polarization. As an example, such schemes for polarization diagnostics of particle and photon beams are required for exploring atomic parity violation phenomena [59,71].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, these measurements demonstrated that utilizing theoretical estimates of the polarization transfer characteristics enables an accurate reconstruction of the incident beam polarization. As an example, such schemes for polarization diagnostics of particle and photon beams are required for exploring atomic parity violation phenomena [59,71].…”
Section: Introductionmentioning
confidence: 99%